2021
DOI: 10.3390/healthcare9121650
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Practices towards Food Poisoning among Parents in Aseer Region, Southwestern Saudi Arabia

Abstract: Background: Food poisoning is caused by eating contaminated food. Improper food safety knowledge, poor food handling, and inadequate personal hygiene may allow microbes to grow in sufficient numbers to cause a food-borne illness. The aim of this paper was to assess the knowledge, attitudes, and practices regarding food poisoning and its determinants of parents in the Aseer region of Saudi Arabia. Methodology: This is a descriptive cross-sectional study conducted on 3011 parents in the Aseer region in the south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…In this study, findings supported that most respondents reported that their mothers are the ones responsible for food preparation. This is consistent with other studies reporting that mothers’ contribution to cooking is more than that of other family members (Ashkanani et al, 2021; Mb et al, 2017; Shati et al, 2021; Zyoud et al, 2019). Individuals responsible for preparing food to consider that food prepared outside the home renders them susceptible to food poisoning compared with that prepared inside the home (Meysenburg et al, 2014; Sudershan et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, findings supported that most respondents reported that their mothers are the ones responsible for food preparation. This is consistent with other studies reporting that mothers’ contribution to cooking is more than that of other family members (Ashkanani et al, 2021; Mb et al, 2017; Shati et al, 2021; Zyoud et al, 2019). Individuals responsible for preparing food to consider that food prepared outside the home renders them susceptible to food poisoning compared with that prepared inside the home (Meysenburg et al, 2014; Sudershan et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…Another study also concluded that females are better informed regarding appropriate food handling compared to males (Zeeshan et al, 2017), which was also supported by another published paper that was conducted looking at university students’ knowledge of food poisoning (Osaili et al, 2021). In contrast to this, some studies reported better knowledge regarding food poisoning in males (Ashkanani et al, 2021; Shati et al, 2021). Risky food-related attitudes are more common among people with low education levels and low-income (Farahat et al, 2015; Zyoud et al, 2019).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Compared to our Polish youth, the youth from Jordan or Greece gave, on average, fewer correct answers to questions about food safety (only 46 %) [5]. In turn, young people living in Turkey and Saudi Arabia had a similar level of knowledge as Poles, respectively 57 % and 75 % of correct answers on food safety [47,51]. Studies conducted among adults have shown that knowledge about food safety increases with age and practice: women score higher than men, and younger respondents show the greatest need for additional food safety education [46].…”
Section: Knowledge Of the Definition Of Food Safetymentioning
confidence: 67%